Podnikatelský záměr - Štencl, František (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Diplomová práce se zabývá zhotovením podnikatelského záměru na vybudování a zprovoznění boulder&baru. Návrh podnikatelského záměru vychází ze shromážděných informací, analýzy současného stavu oboru a nalezení tržní příležitosti.

This master’s thesis deal with processing of business plan for the establishment of boulder&bar. Prospectus project results from accumulated information, analysis of present state of specialization and arises from finding of market opportunity.
Business Plan
Keywords: Boulder; marketingový plán; finanční plán; marketingový mix; SWOT; Cash-flow; Boulder; marketing plan; financial plan; Marketing mix; SWOT; Cash flow